Historical reconfigurations of a social–ecological system adapting to economic, policy and climate changes in the French Alps - Bruley, E.; Locatelli, Bruno; Vendel, F.; Bergeret, A.; Elleaume, N.; Grosinger, J.; Lavorel, S. (Springer, 2021)
To ensure their quality of life, people adapt to multiple changes by maintaining or transforming the structure and functions of their socio-ecological systems (SES). A better understanding of mechanisms underpinning SES adaptation, especially the contribution of changes in human–nature interactions, is crucial to facilitate adaptation to future challenges. Using a chronosystemic timeline and based on literature, archives and local knowledge of inhabitants, we explored the past trajectory of a mountain SES (Pays de la Meije, French Alps) since 1900 by analysing drivers, impacts and responses. We hypothesised that adaptation has occurred through changes in the co-production of nature’s contributions to people (NCP). We identified four historical periods of combined changes in agriculture and tourism with associated changes in NCP. Results show which and how drivers of changes have influenced NCP co-production, how NCP have been mobilised in adaptive responses and how human and natural capitals involved in NCP co-production have been reconfigured for adaptation. We show that drivers of change have been mainly exogenous and out of the control of local actors, like public policies, markets and consumption patterns. These drivers can directly impact the capitals involved in NCP co-production like amount of workforce, knowledge or skills, creating not only threats but also opportunities for the livelihood of the local community. Depending on the intensity of capital reconfiguration and the type of NCP involved, adaptive responses range from resistance to transformation of the governance system and socio-economic sectors. This analysis highlights existing path dependencies that could hinder future adaptation.